2014
DOI: 10.1080/02705060.2014.982725
|View full text |Cite
|
Sign up to set email alerts
|

Life-history costs of reproductive behaviors in a wetland-breeding amphibian

Abstract: Studies examining the association between life-history strategies and behavior can help inform our understanding of the fitness consequences of reproductive behaviors. Breeding migrations are common in numerous taxa and often represent an important reproductive cost. We examined body mass changes of spotted salamanders (Ambystoma maculatum) during their seasonal breeding migrations to determine the influence of breeding behaviors on reproductive costs. We sampled salamanders entering and exiting a 0.92-ha ephe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The negative relationship between body condition and ice-on (winter) duration can be reasonably attributed to extended fasting in years of late ice-off. Similarly, later spring capture dates resulted in reduced body condition of females and males, a result corroborated in similar salamander field studies (Homan et al, 2018;Strickland et al, 2015), and likely related to their non-feeding status and energy expenditure throughout winter (Figure 6b) and during early spring migration and breeding. Although we did not forecast how changes in ice-on duration may affect body condition (largely due to the lack of any projection available), it seems likely that warmer fall temperatures will be associated with decreases in winter duration in future climates, and hence relatively warm temperatures in the overwintering environment (Figure 6a), which may partly offset the energetic benefit of a shortened winter duration.…”
Section: Discussionsupporting
confidence: 80%
“…The negative relationship between body condition and ice-on (winter) duration can be reasonably attributed to extended fasting in years of late ice-off. Similarly, later spring capture dates resulted in reduced body condition of females and males, a result corroborated in similar salamander field studies (Homan et al, 2018;Strickland et al, 2015), and likely related to their non-feeding status and energy expenditure throughout winter (Figure 6b) and during early spring migration and breeding. Although we did not forecast how changes in ice-on duration may affect body condition (largely due to the lack of any projection available), it seems likely that warmer fall temperatures will be associated with decreases in winter duration in future climates, and hence relatively warm temperatures in the overwintering environment (Figure 6a), which may partly offset the energetic benefit of a shortened winter duration.…”
Section: Discussionsupporting
confidence: 80%
“…Unfortunately, we were unable to estimate intra‐annual breeding dispersal distances of females due to low recapture rates within breeding seasons. However, it is likely that the high physiological and ecological costs associated with breeding (Strickland et al, 2015) prohibit female movement between wetlands, particularly those located in different clusters, within a breeding season. Of the 339 females we recaptured over the study period, we only observed 10 within‐year movement events.…”
Section: Discussionmentioning
confidence: 99%
“…The wetland is surrounded by deciduous and pine forest and is dominated by tall grassy vegetation (Pittman et al 2008). Every day at approximately 1000 hours, we sampled 38 pitfall traps (13-L plastic buckets) placed every 10 m on the inside of a 400-m drift fence completely encircling the wetland (Strickland et al 2014). Two 61 9 122-cm wooden cover boards were placed on the inside of the drift fence.…”
Section: Methodsmentioning
confidence: 99%